2020
DOI: 10.1007/s00268-020-05820-8
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Implementing Artificial Intelligence into Surgical Practice

Abstract: Background Artificial intelligence is touted as the future of medicine. Classical algorithms for the detection of common bile duct stones (CBD) have had poor clinical uptake due to low accuracy. This study explores the challenges of developing and implementing a machine‐learning model for the prediction of CBD stones in patients presenting with acute biliary disease (ABD). Methods All patients presenting acutely to Christchurch Hospital over a two‐year period with ABD were retrospectively identified. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Internal audit (unpublished data) identified that only 40% of MRCPs performed identified choledocholithiasis, while over 90% of patients would have been suitable for up front LC and IOC. Several preoperative decision scores are available to stratify the risk of CBD stones using a combination of LFTs and preoperative imaging 24,25 . Despite improved performance over ad hoc, clinical decision making their use in practice is not routine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal audit (unpublished data) identified that only 40% of MRCPs performed identified choledocholithiasis, while over 90% of patients would have been suitable for up front LC and IOC. Several preoperative decision scores are available to stratify the risk of CBD stones using a combination of LFTs and preoperative imaging 24,25 . Despite improved performance over ad hoc, clinical decision making their use in practice is not routine.…”
Section: Discussionmentioning
confidence: 99%
“…Several preoperative decision scores are available to stratify the risk of CBD stones using a combination of LFTs and preoperative imaging. 24,25 Despite improved performance over ad hoc, clinical decision making their use in practice is not routine. Initial LC for patients at intermediate risk of CBD stones has been shown to reduce LOS and cost without compromising patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Tranter‐Entwistle et al . explored the potential usefulness of AI for predicting common bile duct stones in patients with acute biliary disease and achieved a sensitivity of 37% and a specificity of 96% based on the results of blood tests 49 . Notably, in that study, the authors described challenges posed by coding errors and missing data in real‐world clinical data, highlighting the hurdles of such research and the need for large datasets to achieve adequate model performance.…”
Section: Biliary Diseasesmentioning
confidence: 99%
“…Multiple studies have briefly touched on some of the difficulties of implementing AI in procedural specialties and practices. 10,13,17,20,39,40 Here, we break down the most significant of these challenges in the following categories: inherent specialty challenges, regulatory challenges, intellectual property, raising capital, and ethical challenges.…”
Section: Challenges Of Implementing Artificial Intelligencementioning
confidence: 99%